2010
DOI: 10.1063/1.3446869
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of structural defects associated with electrical degradation in AlGaN/GaN high electron mobility transistors

Abstract: We have investigated the surface morphology of electrically stressed AlGaN/GaN high electron mobility transistors using atomic force microscopy and scanning electron microscopy after removing the gate metallization by chemical etching. Changes in surface morphology were correlated with degradation in electrical characteristics. Linear grooves formed along the gate edges in the GaN cap layer for all electrically stressed devices. Beyond a critical voltage that corresponds to a sharp increase in the gate leakage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
115
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(119 citation statements)
references
References 20 publications
3
115
1
Order By: Relevance
“…Following the electrical stress experiment, a three-step process 9,19 was followed to remove the passivation and metal contacts from the surface of the devices. Our chemical techniques are rather benign on GaN.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the electrical stress experiment, a three-step process 9,19 was followed to remove the passivation and metal contacts from the surface of the devices. Our chemical techniques are rather benign on GaN.…”
Section: Methodsmentioning
confidence: 99%
“…We find similar pit and trench formation under the gate edge on the drain side as observed by other authors after stress in the OFF-state regime. 19,20 In a new finding, this damage strongly correlates with the degree of drain current degradation suffered by the device. Channel temperature was found to be an accelerating factor of this type of structural degradation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to increase the lifetime of AlGaN/GaN HEMTs, it is essential to have a detailed understanding of the mechanisms underlying the degradation of these devices. It has previously been reported that the gate leakage current, I g , degrades when the devices are operated in pinched off conditions or when the gate Schottky contact is reverse biased 2,3,4,5,6,7,8,9,10,11,12 . Some reports have correlated the increase in I g during offstate stress of the devices with the appearance of grooves and v-shaped pits on the surface of the semiconductor, located at the edges of the gate contact 6,7,9,12 .…”
mentioning
confidence: 99%